2005
DOI: 10.3354/dao065227
|View full text |Cite
|
Sign up to set email alerts
|

Lectin blot studies on proteins of Myxobolus cerebralis, the causative agent of whirling disease

Abstract: It is known that Myxobolus cerebralis antigens, both surficial and secreted, are key modulators for, or targets of, host immune system compounds. We undertook SDS-PAGE glycoprotein characterisation of M. cerebralis developmental stages isolated from infected rainbow trout and Western blot analyses using selected biotin-labelled plant lectins (GSA-I, PHA-E, SJA, GSA-II) and anti-triactinomyxon polyclonal antibodies. Glycoproteins were isolated with lectin-affinity chromatography, and prominent bands were charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
(50 reference statements)
1
9
0
Order By: Relevance
“…Pre-esporogonic and extra-esporogonic stages of T. bryosalmonae were also stained by BSI-I at LM (Marín de Mateo et al 1996;Morris and Adams 2004), though only some vacuolar structures of P cell were scarcely labelled at TEM (Morris and Adams 2004). Using blot studies, Knaus and El-Matbouli (2005b) identified glycoproteins that contained carbohydrate motifs reactive with the same lectin in Myxobolus cerebralis stages as well.…”
Section: Discussionmentioning
confidence: 96%
“…Pre-esporogonic and extra-esporogonic stages of T. bryosalmonae were also stained by BSI-I at LM (Marín de Mateo et al 1996;Morris and Adams 2004), though only some vacuolar structures of P cell were scarcely labelled at TEM (Morris and Adams 2004). Using blot studies, Knaus and El-Matbouli (2005b) identified glycoproteins that contained carbohydrate motifs reactive with the same lectin in Myxobolus cerebralis stages as well.…”
Section: Discussionmentioning
confidence: 96%
“…Such terminal sugar re sidues are believed to play a paramount role in host− parasite interactions and may form a protective sheath for the parasites that helps them to evade host recognition (Hicks et al 2000, Theodoropoulos et al 2001. Therefore, some parasites, such as Trypanosoma cruzi (Buscaglia et al 2006), employ an antigen variation strategy through modification of N-and Oglycosides of glycoepitopes in their surface glycoproteins (Gagneux & Varki 1999, Knaus & El-Matbouli 2005. In fish, as in all vertebrates, the lectin pathway of the complement system is an ancient first line defense mechanism of the innate immune system that relies on recognition of pathogen-associated glycan epitopes (Sunyer & Lambris 1998, Nakao et al 2006, Kania et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…In fish, as in all vertebrates, the lectin pathway of the complement system is an ancient first line defense mechanism of the innate immune system that relies on recognition of pathogen-associated glycan epitopes (Sunyer & Lambris 1998, Nakao et al 2006, Kania et al 2010. In previous studies, the glycoproteins of some piscine parasites have been studied by lectin blotting (Feng & Woo 1998b, Kim et al 1999, Muñoz et al 2000a, Knaus & El-Matbouli 2005.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this approach can be time-and laborconsuming, and detection and identification is mainly based on the mature spore stages, with the early parasite stages likely to be neglected (Grabner et al 2012, Mahony et al 2015. Immunological methods based on antibodies or lectins (Knaus & El-Matbouli 2005, Estensoro et al 2013) have also been developed. Nevertheless, these methods are generally restricted by cross-reactivity between different species (Lu et al 2002, Estensoro et al 2014, Jia et al 2016.…”
Section: Introductionmentioning
confidence: 99%